اعادة تهيئة المدخل الشمالي لمدينة بريان في اطار التنمية الحضرية المستدامة - سعدي, مصعب امين; Salhi, Atef, Directeur de thèse (My University, 2020)
My project consists in the urban re-planning of the northern entrance of Berriane city, department of Ghardaia. I did it in the frame of urban sustainable development in order to deal with functional, urban and social problems caused by the absence of a clear urban policy and by the lack of land base. This situation caused a non- organized expansion of the town. The project is divided in three parts. I started by clarifying certain concepts essential to my project, for that I proceeded at the analysis of three examples which are: the Clichy city entrance (France), the Pulversheim city entrance (France) as well as the Seraing town entrance (Belgium). The second part consists in the urban study of Berriane and its characteristics. The survey aimed at getting a clearer image and a better knowledge of the town. To reach this aim I made a poll among a citizens panel. Finally this survey led to the re-planning of the northern entrance of Berriane city in order to create a new urban pole in adequacy with the urban sustainable development principles to apply the concepts and the ideas previously treated and thus for a better image of the town
Laghouat : Université Amar Telidji - Département d'architecture Option : Habitat et politique de ville